Pengaruh Customer Experience, Complaint Handling ,Customer Value, E-Service Quality, terhadap Customer Loyalty dengan Customer Satisfaction sebagai Variabel Intervening: (Studi Kasus di Klinik Kecantikan Dr. Glennarda, Sp.KK) - Azizah, Liza; Suciningtyas, Santi; Handayani, Tri; Prasetyo, Arif Hadi (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2024)
The purpose of this study was to determine and analyze the effect of Customer Experience, Complain Handling, Customer Value, and E-Service Quality on Customer Loyalty with Customer Satisfaction as an Intervening variable, both direct and indirect effects. This study used purposive sampling and accidental sampling techniques with a sample of 100 respondents, the analysis technique used SPSS Version 26.0 with validity test, reliability test, multiple linear regression analysis, significance testing (t test), path analysis and Sobel. Customer Experience (X1) shows a significant influence on Customer Loyalty (Y), Complain Handling (X2) shows a significant influence on Customer Loyalty (Y), Customer Value (X3) shows a significant influence on Customer Loyalty (Y), E-Service Quality (X4) shows a significant influence on Customer Loyalty (Y), there is a significant influence between Customer Experiene (X1) on Customer Loyalty (Y) with Customer Satisfaction (Z) as an intervening variable, there is a significant influence between Complain handling (X2) on Customer Loyalty (Y) with Customer Satisfaction (Z), there is a significant influence between Customer Value (X3) on Customer Loyalty (Y) with Customer Satisfaction (Z) as an Intervening variable, there is a significant influence between E-Service Quality (X4) on Customer Loyalty (Y) with Customer Satisfaction (Z) as an Intervening variable, the Customer Satisfaction (Z) variable has a significant influence on Customer Loyalty (Y). Keywords: customer experience, complain handling, customer value, e-service quality, customer loyalty dan customer satisfaction.